Essential oils in Asia: A systematic review of health outcomes, traditional practices, and socio-economic dimensions - Mohamad Syahrul Nizam Ibrahim; Avelinah Julius; Carlos Silvester (Human Resource Management Academic Research Society (HRMARS), 2025)
This systematic literature review examines the roles of essential oils in Asia across three major dimensions: health and biological effects, wellness and traditional practices, and production with socio-economic significance. Essential oils are widely used for therapeutic, cultural, and economic purposes, yet existing knowledge remains fragmented, creating a gap in integrating biomedical evidence, cultural practices, and production dynamics. The objective of this study is to synthesize available research to provide a comprehensive overview and to highlight gaps that hinder the full potential of essential oils in the region. Following the PRISMA framework, an extensive database search was conducted and fifteen eligible studies were analyzed. The results were categorized into three themes: (1) health and biological effects, including antimicrobial, anticancer, anti-inflammatory, neuroprotective, and vector-control properties; (2) wellness and traditional practices, where essential oils are embedded in cultural health systems such as Batak steam-bathing and Thai massage, serving both therapeutic and identity-preserving roles; and (3) production and socio-economic aspects, where improvements in cultivation, extraction, and processing enhance yield, quality, rural livelihoods, and export economies. Despite these contributions, gaps remain as clinical validation is still limited, socio-economic studies often overlook labor, gender, and community participation, and Malaysian research—especially on Bornean biodiversity and traditional practices—remains scarce. Addressing these gaps will help position essential oils as strategic resources that advance human health, safeguard cultural heritage, and promote sustainable socio-economic development across Asia.